First Evidences of Epithelial-Mesenchymal Transition and Cancer Stem-Cell Phenotype Acquisition in Dermo-Epidermal Junction of BPV-Infected Neoplasms - Rodrigo Pinheiro Araldi; Rafael Guilen de Oliveira; Gabriela Mattoso; Gabriela Casarin; Diego Grando Módolo; Jacqueline Mazzuchelli-de-Souza; Rodrigo Franco de Carvalho; Diva Denelle Spadacci Morena; Willy Beçak; Rita de Cassia Stocco (Journal of Biotechnology and Biomedical Science, 2017)
Introduction Bovine papillomavirus (BPV) is the etiological agent of bovine papillomatosis, infectious and neoplastic disease, characterized by the presence of multiple papillomas that can regress spontaneously or to persist and progress to malignancies when in association with environmental cofactors. Although recognized that the BPV can induce DNA damages, the viral role following cancer initiation remains unresolved. Based on this, we stablished cell lines derived from cutaneous papilloma, fibropapilloma and esophageal carcinoma to study the BPV action on epithelial-mesenchymal transition (EMT). Our results showed strong evidences that the virus action can contribute to EMT and, therefore, metastasis. Aim In this study, we analyzed the expression levels of the EMT markers (cytokeratin 10, STAT3 Y705, Oct-3/4 and vimentin) in paraffin-embed samples, using the same tissues that originated the cell lines previous studied, aiming to validate the results observed using cell lines. Material and Methods Expression levels of these markers was analyzed by immunohistochemistry and the collagen composision by Picrosirius red staining. Results We verified an overexpression of these markers in fibroblastoid cells present into the epidermis and ketarinocyte-like cells into the dermis present in dermo-epidermal junction. These data reinforce our previous results using cell cultures, validating both systems (cell culture and paraffin-embed tissues) as useful models to study the natural history of BPV-infected lesions. Conclusion Altogether, the results from these systems indicate that the BPV promote the cancer progression and metastasis through the transdifferentiation of an epithelial to mesenchymal cells (EMT).
Keywords: BPV